Vídeo educativo como tecnologia de apoio à prevenção do câncer de colo uterino - Anjos, Saiwori de Jesus Silva Bezerra dos (2011)
We emphasize education as a major factor that seeks human emancipation, quality of life and reduce vulnerability related to cervical cancer. The objective was to develop, implement and assess the result of the use of an educational video focusing on health promotion of knowing the purpose, frequency, pre-examination care and proper attitude for the prevention of cervical cancer. Evaluation research, quasi-experimental, cross-sectional and quantitative, carried out in four stages: development of the video script; assessment of the script; recording and video editing; implementation and assessment of the video. The sample was composed of seven content analysts, three technical analysts and 162 women living in the coverage area of two family health teams in the city of Fortaleza, Ceará. The workshops of video presentation happened in 12 meetings in September 2011 in support points of the community. We used structured evaluation form for the analysts and Knowledge, Attitude and Practice questionnaire for women in pre and post-test. For analysis we used the statistical tests Chi-square, Likelihood Ratio, Linear Association, T-test and Z-test of proportions with p<0.05. The script was prepared following these steps: idea, conflict, characters, dramatic action, dramatic time and dramatic unity. In its assessment the analysts rated it as very good, with outstanding contributions in the improvement of the final script. The sample was characterized by young adults between 25 and 59 years (58.6%), mean age 40.8 (SD = 17.9), low education (up to nine years of study - 63.7%) and low income (up to a minimum salary - 61.1%, mean 742.4, SD = 528.2), housewives (50%), married or in stable relationships (57.4%), Catholic (66%) and brown skin (70.4%). The women in study presented, mostly, proper practice on the Pap smear screening (81.5%), appropriate frequency of up to three years between examinations (71.3%), with date of last test within recommended levels (mean of 20.34 months). Although women demonstrated appropriate practice, the knowledge before the educational activity was insufficient regarding the purposes other than the prevention of cervical cancer associated with the report of not knowing the purpose (32.7%). The educational activity mediated by video was effective when it comes to increase the knowledge of the purpose of the Pap smear screening (29.6 percentage points) (p = 0.001), increased pre-test care mentioned, 2 or 3 care (22.2 percentage points) or 4 cares increased significantly (25.9 percentage points) (p = 0.000). There was an increase in the number of women who reported appropriate frequency (13 points) with significant correlation in the ones reporting on the frequency of 3/3 years with two normal tests (p = 0.001). The information spread by educational video contributed to change the attitudes of women that after the video increased the percentage of proper attitude (11.1 points). The reason for the proper attitude (prevent cervical cancer) increased 27.7 percentage points (p = 0.001). We conclude that the educational video promotes knowledge on the purpose, frequency and pre-examination care and proper attitude for the prevention of cervical cancer.